Rural houses heating costs - Manteuffel-Szoege, Henryk (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2008)
Average full (including capital, operation and maintenance costs) annual heating costs in a standard family house with 180 m2 of floor surface are compared for various heating systems under the Polish economic conditions. The compared heating technologies comprise water to water and ground loop heat pumps with both vertical and horizontal loops, a liquid gas combustion furnace, an earth gas combustion furnace, a coal combustion furnace, a straw combustion furnace, a wood combustion furnace and an electric stove. A sensitivity analysis with regard to the interest rate and the value of owner’s work did not change the general conclusion that in most cases heat pumps were the cheapest, while oil and coal burning furnaces or an electric boiler the most expensive solutions. The cost of own labour was decisive for the appraisal of labour intensive systems